Ar Daith Olaf - Davies, Alun (Y Lolfa, 2021)
The nightmare of past cases has forced Taliesin to retire as a detective. He takes part in a true crime podcast to keep his mind off the booze. When he and presenter, Mari, receive a link to a real life murder they realise that there are similarities with one of the cases they have been discussing. Who is the murderer and why does he look to. Intro – Taliesin – Mari – Taliesin – Siwan – Mari – Taliesin – MJ – Taliesin – Mari – Taliesin – E – Siwan – Taliesin – Mari – Taliesin – E – Mari – Taliesin – Siwan – Taliesin – Siwan – Taliesin – Mari – Taliesin – E – Taliesin – Mari – Taliesin – Mari – Taliesin – Mari – Taliesin – Mari – Taliesin – E – Mari – Taliesin – E – Mari – Taliesin – E – Mari – E – Taliesin – E – Mari – Taliesin – Mari – Taliesin – E – Taliesin – E – Taliesin – E – Taliesin – E – Taliesin – Siwan – Mari – Siwan – Mari – Siwan – Taliesin – Siwan – E – Taliesin – MJ – Taliesin – MJ – Taliesin – Siwan – Taliesin – E – MJ – Taliesin – E – Mari – Taliesin – E – Taliesin – E – Siwan – E – Taliesin – Siwan – Taliesin – Siwan – E – Taliesin – E – Siwan – Mari – Taliesin – E – Siwan – Taliesin – E – Siwan – E – Taliesin – E – Siwan – Taliesin – E – Siwan – Taliesin – Siwan – Taliesin – E – Taliesin – Siwan – E – Taliesin – Siwan – Mari – Siwan – Mari – MJ – Siwan – Taliesin.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books